What Happens When I Watch a Ballet and I Am Dyskinetic? A fMRI Case Report in Parkinson Disease - Palermo, Sara; Morese, Rosalba; Zibetti, Maurizio; Romagnolo, Alberto; Carlotti, Edoardo Giovanni; Zardi, Andrea; Valentini, Maria Consuelo; Pontremoli, Alessandro; Lopiano, Leonardo (Frontiers in Psychology, 2020)
Background: The identical sets of neurons - the mirror neuron system (MNS) - can be activated by simply observing specific, specific movements, decoded behaviors and even facial expressions performed by other people. The same neurons activated during observation are those recruited during the same movements and actions. Hence the mirror system plays a central role in observing and executing movements. Little is known about MNS in a neurodegenerative motor disorder, such as Parkinson’s Disease (PD) is. Methods: We explored the neural correlates potentially involved in empathy and embodiment in PD through complex action observation of complex behaviors like the choreutical arts. An integrated multidisciplinary assessment (neurological, neuropsychiatric, and neuropsychological) was used for the selection of the PD candidate for the neuroimaging experimental acquisition. For the first time in literature the famous Calvo-Merino’s paradigm was administered to a PD subject. Key points: fMRI exploratory analysis shows the recruitment of the left thalamus, the right dorsolateral prefrontal cortex, and the bilateral superior precentral gyrus (one of the main hubs of the MNS). If the observed choreic movement becomes part of the observer's motor repertoire experience, mirror neurons might activate stimulating affective empathy and making the understanding of movement an own proper body experience (cognitive embodiment). Main lessons: Our study sheds light on a possible use of complex action observation to improve or slow the deterioration of motor abilities and levodopa-induced dyskinesias in PD patients. Indeed, the modulation of the neural area involved in complex action observation could be considered a promising target for neuro-rehabilitative intervention mediated by the elicitation of the MNS.